2021
DOI: 10.1038/s41420-021-00743-2
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal HSP90 inhibitor NCT-58 kills trastuzumab-resistant breast cancer stem-like cells

Abstract: N-terminal HSP90 inhibitors in development have had issues arising from heat shock response (HSR) induction and off-target effects. We sought to investigate the capacity of NCT-58, a rationally-synthesized C-terminal HSP90 inhibitor, to kill trastuzumab-resistant HER2-positive breast cancer stem-like cells. NCT-58 does not induce the HSR due to its targeting of the C-terminal region and elicits anti-tumor activity via the simultaneous downregulation of HER family members as well as inhibition of Akt phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Mammospheres harbor plentiful mammary stem-like cells and the sphere formation assay is an efficient tool for evaluating the effect of CSC targeting drugs [ 31 ]. We have previously reported that stemness-related proteins including ALDH1, Nanog, Oct4, and Sox2 were higher in mammospheres compared to their adherent counterparts [ 32 ]. Formation of mammospheres derived from BT474 and JIMT-1 cells was markedly attenuated in response to β-escin treatment (10-20 μM), as evidenced by a significant decrease in the number and volume of mammosphere formed under anchorage-independent serum-free culture conditions (*** p <0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammospheres harbor plentiful mammary stem-like cells and the sphere formation assay is an efficient tool for evaluating the effect of CSC targeting drugs [ 31 ]. We have previously reported that stemness-related proteins including ALDH1, Nanog, Oct4, and Sox2 were higher in mammospheres compared to their adherent counterparts [ 32 ]. Formation of mammospheres derived from BT474 and JIMT-1 cells was markedly attenuated in response to β-escin treatment (10-20 μM), as evidenced by a significant decrease in the number and volume of mammosphere formed under anchorage-independent serum-free culture conditions (*** p <0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mesenchymal-like CD44 high /CD24 low population is an aggressive phenotype, that is highly tumorigenic and more resistant to drugs [ 28 ]. The CD44 high /CD24 low phenotypes account for approximately 0.5% of trastuzumab-sensitive BT474 cells, whereas they account for more than 50% in trastuzumab-resistant JIMT-1 cells [ 32 , 33 ]. In the present study, the CD44 high /CD24 low subpopulations of JIMT-1 cells were as high as 63.4%, and these cell populations were significantly reduced by β-escin challenge (*** p <0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR (125 MHz, CDCl 3 ) δ 186.9, 161.0 (×2), 152.1, 138.9, 137.8, 128.9, 105.9 (×2), 101.9, 96.1, 55. 5 1E,4E)-1-(Benzoijd]ij1,3]dioxol-4-yl)-5-(methylamino)penta-1,4-dien-3-one (1q) (20% yield); yellow oil. 1 H NMR (600 MHz, CDCl 3 ) δ 10.24 (s, 1H), 7.42 (d, J = 15.9 Hz, 1H), 6.94 (dd, J = 7.9, 0.9 Hz, 1H), 6.88 (d, J = 15.9 Hz, 1H), 6.84 (dd, J = 12.7, 7.2 Hz, 1H), 6.80 (d, J = 7.8 Hz, 1H), 6.77 (dd, J = 7.7, 1.1 Hz, 1H), 6.04 (s, 2H), 5.20 (d, J = 7.1 Hz, 1H), 3.06 (d, J = 4.9 Hz, 3H).…”
Section: Chemistrymentioning
confidence: 99%
“…Although the potency of Hsp90 CTD inhibitors has improved significantly compared to novobiocin, the scaffold diversity is still scarce. Known inhibitors include novobiocin analogues, analogues of other natural products such as deguelin, EGCG, silybin and scaffolds already established as inhibitors of other targets, e.g., benzothiazole-based DNA gyrase B inhibitors ( 4–9 , Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. To expand the structural diversity of Hsp90 CTD inhibitors, we performed structure-based virtual screening to discover novel scaffolds.…”
Section: Introductionmentioning
confidence: 99%